A Step Forward?: Exploring the diffusion of data journalism as journalistic innovations in China. (4th July 2019) - Zhang, Shuling; Feng, Jieyun
Abstract : Drawing on Rogers' diffusion of innovation theory and Moore's concept of chasm, this paper investigates how data journalism is locally adopted and historically embedded in China, as well as what facilitates or impedes its diffusion into the country's media practices. A combined study of content analysis (n = 290) and semi-structured interviews with 20 Chinese media practitioners shows that despite enthusiasm for implementing this innovative form of journalism, it is only practiced at a cursory level with differences observed among traditional media, internet portals, and new media. While practitioners see clear advantages in data-driven sense-making and storytelling, there remains skepticism among those who doubt its compatibility with China's existing media system and have complexity concerns, or else are perplexed about its trialability in the context of a compressed innovation cycle. China's insufficient inheritance of quantitative reporting tradition and its long-held synthetic cognitive mode, together with the predicament of data availability and buffering tactics deployed by Chinese media to tackle uncertainties, all call into question how far data-driven journalistic innovation can extend its reach in the Chinese context.